Endoscopic and pathohistologic features of early gastric signet ring cell carcinoma presented as elevated type: A case report - Di, Lianjun; Wu, Xinglong; Tuo, Biguang (Frontiers in Oncology, 2022)
Background Almost all early gastric signet ring cell carcinomas (SRCCs) are the flat or depressed type, and the elevated type is rare. Here, we report the endoscopic and pathohistologic features of a rare case of SRCCs presented as the elevated type. Case presentation A 54-year-old man underwent esophagogastroduodenoscopy in our hospital because of intermittent upper abdominal pain for 6 years. White light endoscopy revealed an elevated lesion that is smooth and reddish and covered with normal mucosa and looked like a polyp. Magnifying endoscopy with narrow-band imaging showed broadened intervening parts, an elongated pit, and a dense microvascular network with focal irregularity. The lesion was considered as early gastric cancer and completely resected with endoscopic submucosal dissection. Pathohistological examination confirmed that the lesion was pure early SRCC that was limited within the mucosal lamina propria (T1a). Conclusion Elevated pure gastric SRCC is rare. This is a report of early pure gastric SRCC presented as the elevated type and the description of its endoscopic and pathohistologic features, which will contribute to the early detection of gastric SRCC.